2010
DOI: 10.1103/physrevlett.105.248103
|View full text |Cite
|
Sign up to set email alerts
|

4D Traction Force Microscopy Reveals Asymmetric Cortical Forces in MigratingDictyosteliumCells

Abstract: We present a 4D (x; y; z; t) force map of Dictyostelium cells crawling on a soft gel substrate. Vertical forces are of the same order as the tangential ones. The cells pull the substratum upward along the cell, medium, or substratum contact line and push it downward under the cell except for the pseudopods. We demonstrate quantitatively that the variations in the asymmetry in cortical forces correlates with the variations of the direction and speed of cell displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
113
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 22 publications
11
113
2
Order By: Relevance
“…Previous studies have reported downward pushing forces into the substrate that suggested a role for nuclear compression (22,25), but we find minimal forces exerted in the nuclear and perinuclear regions. This discrepancy may result from differences in cell type (fibroblasts vs. endothelial cells or Dictyostelium), cell shape (spread vs. round), hydrogel rigidity (∼6.5 kPa in this study vs. 400 Pa, ∼4 kPa for previous studies), or spatial resolution of the different TFM methods.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous studies have reported downward pushing forces into the substrate that suggested a role for nuclear compression (22,25), but we find minimal forces exerted in the nuclear and perinuclear regions. This discrepancy may result from differences in cell type (fibroblasts vs. endothelial cells or Dictyostelium), cell shape (spread vs. round), hydrogel rigidity (∼6.5 kPa in this study vs. 400 Pa, ∼4 kPa for previous studies), or spatial resolution of the different TFM methods.…”
Section: Discussioncontrasting
confidence: 46%
“…Interestingly, recent studies have demonstrated that cells on planar substrata exert significant vertical (normal) tractions, indicating that patterns of cellular force generation are more complex than previously thought (22)(23)(24)(25). However, mapping these multidimensional traction stresses with a high spatiotemporal resolution has been challenging, and there is no clear agreement on the dynamics and the location of the normal stresses.…”
mentioning
confidence: 94%
“…The schematic illustration in Figure 5E shows the suggested mechanism of how cell tension creates a pushing force against the rigid substrate on convex spherical geometries while a pulling force is created on concave ones – with a consequential impact on the nuclear morphology. Such a push‐pull mechanism was already presented by Delanoë‐Ayari and co‐workers for flat surfaces 34. It describes that tensile cytoskeletal (pull) forces pointing from the focal adhesions toward the cell's center create significant downward orientated compressive (push) forces at the nucleus 34, 35.…”
Section: Resultsmentioning
confidence: 87%
“…Such a push‐pull mechanism was already presented by Delanoë‐Ayari and co‐workers for flat surfaces 34. It describes that tensile cytoskeletal (pull) forces pointing from the focal adhesions toward the cell's center create significant downward orientated compressive (push) forces at the nucleus 34, 35. On very soft materials this leads to a deformation of the substrate rather than of the nucleus (see34, 35 for detailed explanation).…”
Section: Resultsmentioning
confidence: 87%
“…This means that actomyosin contractility is triggered by the same molecular signal (probably calcium level [5]) whatever its fine structure (filamentous cortex or fibrils). For amoeboid microplasmodia, one can estimate the cortical tension transmitted to the substrate by simply dividing the peripheral force by the perimeter L, t C ¼ F/L ¼ 5-20 mN m 21 , a value intermediate between the ones previously measured for Dictyostelium at single cell and slug stages, respectively [11,18]. For chain type microplasmodia, assuming that the force per contractile unit (typically about 5 mN) is mostly transmitted all around a ring of about R ¼ 50 mm radius (dotted line in figure 8a), we can estimate a head tension t H ¼ F=2pR ≃ 30 mN m À1 , a value quite similar to t C .…”
Section: Discussionmentioning
confidence: 99%